Synthesis and Biological Activity of 1,3-Oxazpine-4,7-Dione Derivatives - Ameen Abd El-Jabbar, Ban; Watheq, Baraa; A. Jawad, Asmaa; Khalid Ibrahim, Halah; K. Al-Rubai, Haider (Al-Nahrain Journal of Science, 2024)
The compounds 1,3-oxazepine-4,5-dione (C and D) are generated by reacting schiff base derivatives (A and B) with succinic anhydride. The Schiff bases (A and B) are obtained via the reaction between benzidine and 4-hydroxycinnamaldehyde, 4-dimethylaminocinnamaldehyde, resulting in the formation of Schiff bases. All synthesized derivatives are characterized based on their physical characteristics and spectrum methods, such as FTIR and 1HNMR. These compounds were shown to possess antibacterial and antifungal properties and demonstrated significant effectiveness against all the microorganisms tested. The derivative of 1,3-oxazepine,4,5-dione (C) has an effect on zone inhibition on antimicrobial agents such as Staphylococcus aureus, Escherichia coli, and Bacillus subtilis at 34, 25, and 29 mm, respectively, which gives higher activity from the derivative (D). It was found that oxazepine derivatives (C and D) are more effective than Schiff base derivative (B) against all fungi that were tested, including Aspergillus niger and Chalara corda.